The Educative Role of Social Reintegration Programs on Desistance from Crime - Laura-Julia Koblicska (Research and Education, 2022)
Social reintegration programs carried out within probation services are an important factor contributing to desistance from crime. A large number of people in the records of these services have the obligation to participate in at least one such program. It is known that the programs carried out by the probation officers have a significant educational component on the supervised persons, as they include many of the elements of an effective correctional treatment. It was also observed that delinquents participating in these programs develop thinking techniques that help them carefully evaluate the consequences of their own decisions and actions. The topic of this paper represents a real interest for probation practitioners, since the development of the supervision process, the preparation of educational reintegration programs in the activity of assistance and counselling, require interactions with the beneficiaries of the Probation Services. Therefore, the emergence of some situations may inherently present professional ethical dilemmas. This paper highlights the need to explore and analyse the nature of these dilemmas, their frequency, the way counsellors manifest themselves in the face of an ethical ambiguity, the highlighting of optimal answers and reactions from a deontological and ethical point of view, and finally, the creation of some good practices. Although the chosen subject is an extremely challenging one, in this paper I will focus on the counsellor-beneficiary relationship, being aware of the multitude of issues that can be discussed with colleagues from different services. I will mention general aspects related to the notions of relevant aspects in the Romanian legislation and in the European recommendations in the matter of probation. The present study was carried out at the national level, namely at the level of the Probation Services between 15.10.2022 and 14.11.2022. The research was built on the basis of the sociological survey method and as an investigation tool we used questionnaires. Which included both closed and open questions. Also, to obtain information, I used other techniques, such as the study of documents (probation files) and open-ended discussions. The data were collected by completing the questionnaires to the probation counsellors through remote communication means, and personally by colleagues from the Bistrița-Năsăud Probation Service. Thus, a number of 50 colleagues from most services in the country agreed to complete the questionnaire. In the last part of the paper, as a result of the research undertaken, I aimed to present the way in which we analyse and manage a variety of professional ethical dilemmas encountered in everyday practice. In addition, the relevant legislative benchmarks are discussed, optimized response strategies are presented, and finally the conclusions represent an opportunity for reflection and learning that can provide professionals with greater self-confidence, and a sense of safety and control over these situations.